Konversi Lahan Pertanian Dan Dampaknya Terhadap Kesejahteraan Petani Dan Ketahanan Pangan Di Provinsi Bali - A.A.A, I Made Sudarma; Sawitri Dj, Wulandira; Bagus Dera Setiawan, I Gede (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
Land conversion is a logical consequence of increasing activity and population as well as other development processes. Land conversion is a natural thing to happen, but in reality, land conversion is a problem because it occurs on agricultural land that is still productive. The purpose of this study was to determine the factors that influence the conversion of agricultural land; know the impact of conversion of agricultural land on the welfare of farmers; and understanding the impact of the conversion on food security. Data analysis used in this study was factor analysis using a computer with the SPSS 19.0 program package. Based on the results of the research, the conclusion that can be drawn from this research is that the main factors driving land conversion are external and internal. The dominant external factors driving conversion are increased land requirements, more promising jobs in other sectors, uncertainty in the price of agricultural products (price fluctuations), and difficulties in finding workers in the agricultural sector. Internal factors driving land conversion are difficulties in obtaining water resources, high risk, and economic pressure; there was an increase in the income of Subak Gadon farmers on an average of IDR 240,650/are/month as a result of farmers converting land from paddy fields to utilization for business ventures. Land conversion does not affect the food security of farming families but affects food supply at the regional level.